OPTIMIZING THE ROLE OF THE ELECTION SUPERVISORY COMMITTEE IN HANDLING ELECTION ADMINISTRATIVE VIOLATIONS IN ACEH PROVINCE - Ferry Irawan Nasution; Surya Perdana; Cakra Arbas (JHR (Jurnal Hukum Replik), 2023)
The Authority of the Election Supervisory Body in the Process of Resolving Administrative Violations of Elections has been regulated by Law Number 7 of 2017. The Election Supervisory Body has the authority to issue final decisions. With this authority, the role of the Election Supervisory Body is strengthened in the law enforcement framework for electoral justice. This research aims to determine how this authority is implemented, especially in the Province of Aceh. The selection of Aceh Province as the research object is due to the increased cases handled by the Election Supervisory Body in the 2019 Elections compared to 2014. The problem formulations for this journal are: How is the Authority of Election Supervisory Committee in Handling Administrative Violations of Elections? What is the Mechanism for Handling Administrative Violations of Elections? and What Factors Influence the Election Supervisory Committee in Resolving Administrative Violations of Elections in the 2019 Elections? This research is normative legal research accompanied by supporting data. Research data was collected through a literature study. The analysis was carried out using qualitative methods. Based on the research results, it is concluded that the institutional strengthening of election oversight has developed with each decade of electoral implementation, manifested through revisions of laws governing the authority of the Election Supervisory Body. Second, the Election Supervisory Body has issued Regulation Number 7 of 2017 concerning the Handling of Findings and Reports of Electoral Violations and Regulation Number 8 of 2018 concerning resolving administrative violations of elections. Third, factors influencing the Election Supervisory Committee in resolving administrative violations of elections include internal factors such as 1) Human Resource Issues, 2) Facilities and Infrastructure, and 3) Budget.Keywords: Election Supervisory Committee of Aceh, Administrative Election Violations